Personological factors and sexing behaviour among in-school adolescents: implications for counselling psychology (2015)
Text messaging is the most popular form of electronic communication among adolescents. Approximately I in 3 teens send over 100 text messages a day. Recently adolescents have begun to use their cell phones to engage in sexual exploration with one another. This new occurrence has now been labeled as sexting. This new phenomenon includes writing sexually explicit messages, taking provocative pictures of themselves or other individuals, and transmitting these messages using technology. The purpose of this study was to examine personological factors and sexting behaviour among in-school adolescents: implications for counselling psychology. Descriptive research design of ex-post-facto type was used in the study. Multi-stage sampling technique was used in selecting nine hundred and sixty nine (969) participants out of one thousand (1,000) which were randomly selected from ten (10) Local Government Area in Oyo State, Nigeria. The respondents were measured with relevant adopted standardized scale (instruments) and the data obtained was analyzed using the Pearson Product Moment Correlation (PPMC) and Multiple regression statistical analysis of the Statistical Package for the Social Science (SPSS). Three research Questions were raised and answered in the study. The result showed that adolescents' sexting behavior is significantly correlated with: (1) self esteem (r = .640; p<-05) and (2) social networking utilization (r= .659; p<.05), the independent variables (self esteem and social networking utilization) when pulled together have significant contributions to the sexting behavior among adolescents (R (adjusted) =.667 & R2 (adjusted) =.631) and each of the independent variables made a significant contribution to the prediction of sexting behavior among adolescents. In term of magnitude of contribution, social networking utilization made the most significant contribution (Beta= .385; t= 9.43; P<0.05) to the prediction follow by self esteem (Beta= .247; t= 1.62; P<0.05). In view of these findings, the study stressed that the parents/guardians should be enlightened on how to improve on their monitoring towards the students' peer selection and counseling psychologists should intensify their effort to organize seminars/conferences on these factors (such as self esteem and social networking utilization among others) as they significantly influence the sexting behavior among students